COMPARATIVE ANALYSIS OF FIXED ASSETS IN LOCAL GOVERNMENT FINANCIAL REPORTS BY THE SUPERIOR AUDIT AGENCY: (A Study of Reporting Entities in West Java) - Fanikal Zulfari Rizqi; Samugyo Ibnu Redjo; Rahman Mulyawan (DIA: Jurnal Administrasi Publik, 2026)
The purpose of this study is to analyze the comparative use of fixed assets in the financial statements of the West Java Provincial Government by the Supreme Audit Agency (BPK). The method used was qualitative research with descriptive methods. Data collection techniques included interviews, observation, documentation, and triangulation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. This research was conducted at the West Java Provincial Representative Office of the Supreme Audit Agency (BPK). The results indicate that the Financial Statement Audit Cycle was conducted using a risk-based audit approach, encompassing planning, implementation, and reporting of audit results. The most common problem with fixed assets in Bandung City, Garut Regency, and Tasikmalaya Regency was the inaccuracy and inaccuracy of inventory card recording for each balance sheet account in the Regional Government Financial Statements. Efforts were made to optimize fixed asset management, and the BPK consistently provided recommendations and monitored the results of follow-up actions taken by the Regional Governments.